How Can Outdoor Air Pollutants Adversely Affect the Women’s Fertility? Systematic Review - Masoomeh Latifi; Forough Rahim; Mojtaba Ahmadlou; Nima Pouladian; Leili Allahbakhshian (Advanced Biomedical Research, 2024)
In the current century, air pollution is known as one of the most critical environmental problems and it is important to find the relations of air pollution and human health. Various air pollutants, such as volatile organic compounds (VOCs), can negatively affect women’s fertility. An exhaustive electronic search was done from 2013 until July 2023 in PUBMED and The Cochrane Central Register of Controlled Trials. The following keywords were combined using Boolean hints in the databases queried: air pollution AND (fertility OR miscarriage OR embryo quality OR embryo development OR pregnancy OR implantation OR live birth). The randomized controlled trials, case-control and cohort studies analyzing the impact of air pollutants on fertility were included in the review. In this systematic review, a significant relation was found between the increase in air pollution and the reduction of fertility health, live birth rates, embryo quality, fertility, implantation rates, and miscarriage in exposed women. These results suggest low fertility health rates are associated with traffic-related air pollution. This review has concluded four components (particulate matter, nitrogen dioxide, sulfur, and carbon monoxide) of traffic pollution that can impair women’s fertility. Air pollution harms women’s fertility. These effects affect gamete’s quality at the genetic and epigenetic level. These effects also alter fetal development. Studies have also reported an effect on fetal growth with increased miscarriages. Since air pollution is everywhere and has many sources, it seems necessary to increase the awareness of people and government officials, especially in hygiene and health, to limit air pollutants as much as possible.